Kingdom of the Netherlands-Curacao and Sint Maarten : 2019 Article IV Consultation-Press Release and Staff Report; and Statement by the Executive Director for the Kingdom of the Netherlands-Curacao and Sint Maarten. (IMF Staff Country Reports; Country Report, 2020)
This 2019 Article IV Consultation focuses on Curacao and Sint Maarten's near and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. The fiscal position in Curacao improved in the past two years, in part due to implemented fiscal measures. Both Curacao and Sint Maarten would benefit from introducing a Fiscal Responsibility Framework. It could incorporate a central government debt ratio as a long-term anchor and operational rules calibrated to meet it. The report suggests that risks in the financial sector need to be addressed as a matter of priority. The authorities should develop a strategy for addressing financial sector vulnerabilities with the objective of preserving financial stability while minimizing fiscal costs. Significant strengthening of supervision and a complete overhaul of the bank resolution framework are also urgently needed. An across-the board improvement in the governance framework should be a key priority in both countries. Vulnerabilities in the financial system point to the need to strengthen governance in the financial sector.